LIFESTYLE OF RURAL ADOLESCENTS IN HERVEIRAS-RS (Fiep Bulletin - online, 2014)
This descriptive exploratory study is aimed at describing the lifestyle profile of 77 fundamental school 5th and 6th graders, from both genders, ages 10 to 16, of two municipal schools in the rural zone of Herveiras - RS, and the data collection system is based on the inventory of lifestyle habits - EVIA. The daily/habitual actions indicate that the subjects are little active, and most of them do not have the habit of practicing regular physical activities, but when this happens, playing soccer and riding a bicycle are the preferred ones, and are usually carried out around the home (field, lawn). At home, the most common activities consist in watching television and listening to music. Our conclusion was that the study subjects perform everyday actions that demonstrate a little active life in terms of regular physical, sports and leisure activities and, within this context, they end up filling their free time with religious activities. We suggested that the municipal authorities should see to the construction of special facilities (gymnasiums, parks, stadiums) for sports and leisure activities, also in the rural zone, along with socio-cultural projects, at schools and in the community, in order to see to these matters, thus fighting sedentary habits, providing an occupation for the free time and promoting quality of life for the people in the municipality.
Keywords: lifestyle; adolescents; rural zone